Teoria jako ontologiczna retoryka: Rousseau i krystalizacja dyskursu pedagogicznego - Szkudlarek, Tomasz (Kultura-Społeczeństwo-Edukacja, 2019)
Assuming the ontological understanding of rhetoric, as proposed by Ernesto Laclau, the paper explores the language of educational theories in their dimensions significant in terms of the discursive construction of societies. The tropes and rhetorical strategies identified in J.J.Rousseau’s works are assumed as the point of departure for the crystallization of the modern discourse of education, here understood as an ontologically indispensable element of the political.